Review on Dermatophytes Highlighting the Status at National and International Level: A Critical Appraisal. - Marwal, Avinash; Meena, Surendra; Chandra, Subhash; Sharma, Dr. Anima (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Dermatophytes as the name suggest are the fungus that feed on skin. The chief source of their growth is keratin which is widely available in skin, nails and hairs and causes disease in animals and humans due to their ability to obtain nutrients from keratinized material. The organisms colonize the keratin tissues and inflammation is caused by host response to metabolic byproducts. They are usually restricted to the nonliving cornified layer of the epidermis because of their inability to penetrate viable tissue of an immunocompetent host.